src/HOL/Library/Quotient.thy
changeset 35100 53754ec7360b
parent 35099 7722bcb5c37c
child 35101 6ce9177d6b38
child 35103 d74fe18f01e9
--- a/src/HOL/Library/Quotient.thy	Wed Feb 10 17:05:40 2010 +0100
+++ /dev/null	Thu Jan 01 00:00:00 1970 +0000
@@ -1,196 +0,0 @@
-(*  Title:      HOL/Library/Quotient.thy
-    Author:     Markus Wenzel, TU Muenchen
-*)
-
-header {* Quotient types *}
-
-theory Quotient
-imports Main
-begin
-
-text {*
- We introduce the notion of quotient types over equivalence relations
- via type classes.
-*}
-
-subsection {* Equivalence relations and quotient types *}
-
-text {*
- \medskip Type class @{text equiv} models equivalence relations @{text
- "\<sim> :: 'a => 'a => bool"}.
-*}
-
-class eqv =
-  fixes eqv :: "'a \<Rightarrow> 'a \<Rightarrow> bool"    (infixl "\<sim>" 50)
-
-class equiv = eqv +
-  assumes equiv_refl [intro]: "x \<sim> x"
-  assumes equiv_trans [trans]: "x \<sim> y \<Longrightarrow> y \<sim> z \<Longrightarrow> x \<sim> z"
-  assumes equiv_sym [sym]: "x \<sim> y \<Longrightarrow> y \<sim> x"
-
-lemma equiv_not_sym [sym]: "\<not> (x \<sim> y) ==> \<not> (y \<sim> (x::'a::equiv))"
-proof -
-  assume "\<not> (x \<sim> y)" then show "\<not> (y \<sim> x)"
-    by (rule contrapos_nn) (rule equiv_sym)
-qed
-
-lemma not_equiv_trans1 [trans]: "\<not> (x \<sim> y) ==> y \<sim> z ==> \<not> (x \<sim> (z::'a::equiv))"
-proof -
-  assume "\<not> (x \<sim> y)" and "y \<sim> z"
-  show "\<not> (x \<sim> z)"
-  proof
-    assume "x \<sim> z"
-    also from `y \<sim> z` have "z \<sim> y" ..
-    finally have "x \<sim> y" .
-    with `\<not> (x \<sim> y)` show False by contradiction
-  qed
-qed
-
-lemma not_equiv_trans2 [trans]: "x \<sim> y ==> \<not> (y \<sim> z) ==> \<not> (x \<sim> (z::'a::equiv))"
-proof -
-  assume "\<not> (y \<sim> z)" then have "\<not> (z \<sim> y)" ..
-  also assume "x \<sim> y" then have "y \<sim> x" ..
-  finally have "\<not> (z \<sim> x)" . then show "(\<not> x \<sim> z)" ..
-qed
-
-text {*
- \medskip The quotient type @{text "'a quot"} consists of all
- \emph{equivalence classes} over elements of the base type @{typ 'a}.
-*}
-
-typedef 'a quot = "{{x. a \<sim> x} | a::'a::eqv. True}"
-  by blast
-
-lemma quotI [intro]: "{x. a \<sim> x} \<in> quot"
-  unfolding quot_def by blast
-
-lemma quotE [elim]: "R \<in> quot ==> (!!a. R = {x. a \<sim> x} ==> C) ==> C"
-  unfolding quot_def by blast
-
-text {*
- \medskip Abstracted equivalence classes are the canonical
- representation of elements of a quotient type.
-*}
-
-definition
-  "class" :: "'a::equiv => 'a quot"  ("\<lfloor>_\<rfloor>") where
-  "\<lfloor>a\<rfloor> = Abs_quot {x. a \<sim> x}"
-
-theorem quot_exhaust: "\<exists>a. A = \<lfloor>a\<rfloor>"
-proof (cases A)
-  fix R assume R: "A = Abs_quot R"
-  assume "R \<in> quot" then have "\<exists>a. R = {x. a \<sim> x}" by blast
-  with R have "\<exists>a. A = Abs_quot {x. a \<sim> x}" by blast
-  then show ?thesis unfolding class_def .
-qed
-
-lemma quot_cases [cases type: quot]: "(!!a. A = \<lfloor>a\<rfloor> ==> C) ==> C"
-  using quot_exhaust by blast
-
-
-subsection {* Equality on quotients *}
-
-text {*
- Equality of canonical quotient elements coincides with the original
- relation.
-*}
-
-theorem quot_equality [iff?]: "(\<lfloor>a\<rfloor> = \<lfloor>b\<rfloor>) = (a \<sim> b)"
-proof
-  assume eq: "\<lfloor>a\<rfloor> = \<lfloor>b\<rfloor>"
-  show "a \<sim> b"
-  proof -
-    from eq have "{x. a \<sim> x} = {x. b \<sim> x}"
-      by (simp only: class_def Abs_quot_inject quotI)
-    moreover have "a \<sim> a" ..
-    ultimately have "a \<in> {x. b \<sim> x}" by blast
-    then have "b \<sim> a" by blast
-    then show ?thesis ..
-  qed
-next
-  assume ab: "a \<sim> b"
-  show "\<lfloor>a\<rfloor> = \<lfloor>b\<rfloor>"
-  proof -
-    have "{x. a \<sim> x} = {x. b \<sim> x}"
-    proof (rule Collect_cong)
-      fix x show "(a \<sim> x) = (b \<sim> x)"
-      proof
-        from ab have "b \<sim> a" ..
-        also assume "a \<sim> x"
-        finally show "b \<sim> x" .
-      next
-        note ab
-        also assume "b \<sim> x"
-        finally show "a \<sim> x" .
-      qed
-    qed
-    then show ?thesis by (simp only: class_def)
-  qed
-qed
-
-
-subsection {* Picking representing elements *}
-
-definition
-  pick :: "'a::equiv quot => 'a" where
-  "pick A = (SOME a. A = \<lfloor>a\<rfloor>)"
-
-theorem pick_equiv [intro]: "pick \<lfloor>a\<rfloor> \<sim> a"
-proof (unfold pick_def)
-  show "(SOME x. \<lfloor>a\<rfloor> = \<lfloor>x\<rfloor>) \<sim> a"
-  proof (rule someI2)
-    show "\<lfloor>a\<rfloor> = \<lfloor>a\<rfloor>" ..
-    fix x assume "\<lfloor>a\<rfloor> = \<lfloor>x\<rfloor>"
-    then have "a \<sim> x" .. then show "x \<sim> a" ..
-  qed
-qed
-
-theorem pick_inverse [intro]: "\<lfloor>pick A\<rfloor> = A"
-proof (cases A)
-  fix a assume a: "A = \<lfloor>a\<rfloor>"
-  then have "pick A \<sim> a" by (simp only: pick_equiv)
-  then have "\<lfloor>pick A\<rfloor> = \<lfloor>a\<rfloor>" ..
-  with a show ?thesis by simp
-qed
-
-text {*
- \medskip The following rules support canonical function definitions
- on quotient types (with up to two arguments).  Note that the
- stripped-down version without additional conditions is sufficient
- most of the time.
-*}
-
-theorem quot_cond_function:
-  assumes eq: "!!X Y. P X Y ==> f X Y == g (pick X) (pick Y)"
-    and cong: "!!x x' y y'. \<lfloor>x\<rfloor> = \<lfloor>x'\<rfloor> ==> \<lfloor>y\<rfloor> = \<lfloor>y'\<rfloor>
-      ==> P \<lfloor>x\<rfloor> \<lfloor>y\<rfloor> ==> P \<lfloor>x'\<rfloor> \<lfloor>y'\<rfloor> ==> g x y = g x' y'"
-    and P: "P \<lfloor>a\<rfloor> \<lfloor>b\<rfloor>"
-  shows "f \<lfloor>a\<rfloor> \<lfloor>b\<rfloor> = g a b"
-proof -
-  from eq and P have "f \<lfloor>a\<rfloor> \<lfloor>b\<rfloor> = g (pick \<lfloor>a\<rfloor>) (pick \<lfloor>b\<rfloor>)" by (simp only:)
-  also have "... = g a b"
-  proof (rule cong)
-    show "\<lfloor>pick \<lfloor>a\<rfloor>\<rfloor> = \<lfloor>a\<rfloor>" ..
-    moreover
-    show "\<lfloor>pick \<lfloor>b\<rfloor>\<rfloor> = \<lfloor>b\<rfloor>" ..
-    moreover
-    show "P \<lfloor>a\<rfloor> \<lfloor>b\<rfloor>" by (rule P)
-    ultimately show "P \<lfloor>pick \<lfloor>a\<rfloor>\<rfloor> \<lfloor>pick \<lfloor>b\<rfloor>\<rfloor>" by (simp only:)
-  qed
-  finally show ?thesis .
-qed
-
-theorem quot_function:
-  assumes "!!X Y. f X Y == g (pick X) (pick Y)"
-    and "!!x x' y y'. \<lfloor>x\<rfloor> = \<lfloor>x'\<rfloor> ==> \<lfloor>y\<rfloor> = \<lfloor>y'\<rfloor> ==> g x y = g x' y'"
-  shows "f \<lfloor>a\<rfloor> \<lfloor>b\<rfloor> = g a b"
-  using assms and TrueI
-  by (rule quot_cond_function)
-
-theorem quot_function':
-  "(!!X Y. f X Y == g (pick X) (pick Y)) ==>
-    (!!x x' y y'. x \<sim> x' ==> y \<sim> y' ==> g x y = g x' y') ==>
-    f \<lfloor>a\<rfloor> \<lfloor>b\<rfloor> = g a b"
-  by (rule quot_function) (simp_all only: quot_equality)
-
-end